1992
DOI: 10.2337/diab.41.9.1141
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Treatment, Endogenous Insulin Concentration, and ECG Abnormalities in Diabetic Pima Indians: Cross-Sectional and Prospective Analyses

Abstract: The prevalence and incidence of CHD, defined by ECG abnormalities according to the Tecumseh criteria for Minnesota Codes, were determined in Pima Indians greater than or equal to 25 yr of age. In a cross-sectional analysis, the age-sex-adjusted prevalence (+/- SE) of ECG abnormalities was higher in 1454 NIDDM patients (6.86 +/- 0.65%) than in 1696 nondiabetic subjects (3.23 +/- 0.63%; prevalence rate ratio = 2.12; 95% CI 1.39-3.25). In a prospective analysis, the age-sex-adjusted incidence (+/- SE) of ECG abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Indeed, most previous studies were carried out in men, and in the few surveys examining women, no direct relationship was found between insulin and CHD (8,23,26,29). Our finding of similar results in men and women is of particular interest, since it gives support to the idea that hyperinsulinemia (or the underlying insulin resistance, as discussed later) is a risk factor of CHD.…”
Section: Results -Insupporting
confidence: 82%
See 1 more Smart Citation
“…Indeed, most previous studies were carried out in men, and in the few surveys examining women, no direct relationship was found between insulin and CHD (8,23,26,29). Our finding of similar results in men and women is of particular interest, since it gives support to the idea that hyperinsulinemia (or the underlying insulin resistance, as discussed later) is a risk factor of CHD.…”
Section: Results -Insupporting
confidence: 82%
“…Over the last 15 years, the belief has spread that hyperinsulinemia is directly and causally related to CHD. Such a conclusion, which was in agreement with earlier case-control studies reporting that subjects with CHD have higher serum insulin concentrations (15)(16)(17), was supported by a number of cross-sectional and longitudinal population studies (18)(19)(20)(21) but was challenged by several others (22)(23)(24)(25)(26)(27)(28)(29)(30). Moreover, as repeatedly discussed by Jarrett (31,32) and more recently also reiterated by Elliott and Viberti (33) and Wingard et al (34), the arguments in favor of the hypothesis that insulin is an independent risk factor of symptomatic CHD, albeit numerous, are individually weak and altogether not convincing.…”
supporting
confidence: 79%
“…36 Serum insulin and Cpeptide levels have been suggested to be associated with restenosis following percutaneous angioplasties in claudicants and CLI patients. 37 Although it is not clear if the effects of insulin are primarily correlated with worsening of atherosclerotic disease or if it is simply a marker of more severe disease 21,22 and how much of its glycemic control counteracts its direct effects on the vascular system, our results suggest that subdividing the diabetic patients into groups based on their insulin need is reasonable and allows better stratification of patients.…”
Section: Discussionmentioning
confidence: 84%
“…21,22 Few reports on open or endovascular interventions in diabetics have differentiated those requiring insulin for diabetes control and those who did not, 9,11,18 and the conflicting reports may stem from the fact that the patient populations may not be similar in terms of severity of diabetes. The goal of our study was to compare the outcomes in patients with disabling claudication (DC) or CLI to determine if diabetics (DM) have poorer patency, limb salvage (LS), and survival rates than nondiabetic patients and if diabetic regimen affects these outcomes.…”
mentioning
confidence: 97%
“…However, observed differences in manifestations of the IRS among populations with high rates of diabetes and CVD risk factors emphasize the need for caution in generalizing results to similar ethnic groups such as native Hawaiians (6,8,10). For example, prospective studies in Pima Indians found fasting insulin levels predictive of NIDDM but not associated with the incidence of electrocardiographic abnormalities as a marker for heart disease (11). In addition, other features of IRS have been variable in different ethnic populations, even among ethnic groups with similar rates of obesity and diabetes.…”
mentioning
confidence: 92%